PERAN GURU DALAM MENGEMBANGKAN SIKAP SOSIAL MELALUI PEMBELAJARAN IPS DI MTS MIFTAHUSSALAM 1 WONOSALAM DEMAK (Universitas Negeri Semarang, 2023)
Teachers must be able to develop students' social attitudes with their roles so that students can apply social attitudes in everyday life. The purpose of this study was to determine the teacher's role, learning activities, and student responses regarding the development of social attitudes. The research design uses a descriptive qualitative approach. This study uses primary and secondary data sources. Data collection techniques using observation, interviews, and documentation. The data validation technique uses source, data, and time triangulation. Data analysis techniques using data reduction, data presentation, and drawing conclusions. The results of the study show that the teacher carries out his role as a learning resource, facilitator, manager, demonstrator, guide, motivator, and evaluator. Activities in developing social attitudes through social studies learning are planning, application, and evaluation. Student responses related to the development of social attitudes are by accepting, implementing, appreciating, living, and practicing. Guru diharapkan dapat mengembangkan sikap sosial siswa dengan peran yang dimiliki agar siswa dapat mengaplikasikan sikap sosial dalam kehidupan sehari-hari. Tujuan penelitian ini adalah mengetahui peran guru, aktivitas pembelajaran, dan respon siswa terkait pengembangan sikap sosial. Desain penelitian menggunakan pendekatan kualitatif deskriptif. Penelitian ini menggunakan sumber data primer dan sekunder. Teknik pengumpulan data menggunakan observasi, wawancara, dan dokumentasi. Teknik keabsahan data menggunakan triangulasi sumber, data, dan waktu. Teknik analisis data menggunakan reduksi data, penyajian data, dan penarikan simpulan. Hasil dari penelitian bahwa guru menjalankan perannya sebagai sumber belajar, fasilitator, pengelola, demonstrator, pembimbing, motivator, dan evaluator. Aktitivas dalam pengembangan sikap sosial terdiri dari perencanaan, pengaplikasian, dan evaluasi. Respon siswa terkait pengembangan sikap sosial yaitu dengan menerima, menjalankan, menghargai, menghayati, dan mengamalkan.